Variable input constant output 3-phase AC-DC converter - Mohd Izzuddin, Abd Kadir (2010)
Generator which powered by motorcycle engine will produce variable ac voltage because the engine running with difference RPM . If uncontrolled ac-dc converter is used, the output will be unhealthy variable DC voltage and not suitable for charging the battery. This project will use controlled ac-dc converter which will produce considerably constant output dc voltage at variable ac input. The converter uses controllable power switches to produce dc voltage output at 13-15 volt which is then can be use to charge the battery. The benefit of this project is it will be able to control the input from the three- phase generators vehicles specially motorcycle without any problem